2008
DOI: 10.2193/2007-157
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Successful Breeding Pairs for Wolves in the Northern Rocky Mountains, USA

Abstract: Under the Endangered Species Act, documenting recovery and federally mandated population levels of wolves (Canis lupus) in the Northern Rocky Mountains (NRM) requires monitoring wolf packs that successfully recruit young. United States Fish and Wildlife Service regulations define successful breeding pairs as packs estimated to contain an adult male and female, accompanied by ≥2 pups on 31 December of a given year. Monitoring successful breeding pairs will become more difficult following proposed delisting of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(72 citation statements)
references
References 9 publications
2
70
0
Order By: Relevance
“…Mitchell et al (2008) presented models for estimating the number of successful breeding pairs of wolves, b, based on observed pack sizes for six analysis areas within the NRM. Their results suggested that pack size explained much of the variation in the probability that a pack contained a successful breeding pair within the NRM, with models varying across the analysis areas due to differences in growth rate of wolf populations and human-caused mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mitchell et al (2008) presented models for estimating the number of successful breeding pairs of wolves, b, based on observed pack sizes for six analysis areas within the NRM. Their results suggested that pack size explained much of the variation in the probability that a pack contained a successful breeding pair within the NRM, with models varying across the analysis areas due to differences in growth rate of wolf populations and human-caused mortality.…”
Section: Discussionmentioning
confidence: 99%
“…We used a model-based b estimator specific to the six analysis areas developed by Mitchell et al (2008) using data that were collected during and prior to 2005. Pre- Our use of mean pack size to impute missing data for 18 packs among the three states assumed mean pack size was an accurate estimate of expected pack size for those packs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The confidence interval (CI) estimators for probabilities that wolf packs are BPs presented in Mitchell et al (2008) used the standard normal method as an approximation for binomial data on the logit scale, then back-transformed CI endpoints to the probability (0-1) scale. This method is known to have coverage rates that do not match the 100*(1 -a) nominal coverage rate, where a is defined as the type I error rate, particularly for estimated probabilities closer to 0 and 1 than to 0.5 (Jennings 1987).…”
Section: Example Contextmentioning
confidence: 99%